Gaussian and non-Gaussian-based Gram-Charlier and Edgeworth expansions for correlations of identical particles in HBT interferometry - De Kock, Michiel Burger (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Physics))--University of Stellenbosch, 2009.